Implementasi Aplikasi Laporjalanku untuk Pemetaan dan Pelaporan Jalan Rusak di Wilayah Kota Tarakan - Wardani, Ade; Rosyda, Miftahurrahma (Jurnal Saintekom : Sains, Teknologi, Komputer dan Manajemen, 2024)
Tarakan City has road facilities with various degrees of damage, ranging from minor to severe conditions. To address this issue, a WebGIS application is required to provide information about the road conditions. This research aims to develop the "Laporjalanku" application, designed to assist the public in reporting road damage in Tarakan City and mapping information about damaged roads. The application enables the public to easily report complaints via the web or their Android smartphones. Its features include information such as images of damaged roads, the location of damage, and estimated repair times. The development methodology used is the waterfall model, ensuring a systematic and sequential system development process. Black-box testing showed that the system functions well. Meanwhile, the System Usability Scale (SUS) test resulted in a score of 84.5%, categorized as good, and meeting user experience requirements. This application streamlines the road mapping and reporting process, providing accurate information to the Department of Public Works. Additionally, it serves as a vital tool for the government and the public to improve collaboration in maintaining the city's road conditions.